The effect of adult attachment on mobile phone dependence among university students: the mediating role of loneliness - Zhenhong Wang; Zhenhong Wang; Bin Xuan (Frontiers in Psychology)
ObjectiveThis study aimed to examine the direct relationship between adult attachment and mobile phone dependence, as well as the mediating role of loneliness.MethodsUsing a cross-sectional study design, 596 Chinese university students (mean age = 19.8, SD = 1.09; females = 309) completed the Experience in Close Relationship Inventory, the UCLA Loneliness Scale, and the Mobile Phone Addiction Index.ResultsThere were significant differences in loneliness and mobile phone dependence among university students with different adult attachment types. Adult attachment was found to have a significant positive correlation with mobile phone dependence. Moreover, adult attachment had an indirect association with mobile phone dependence through the mediating role of loneliness.ConclusionAdult attachment and mobile phone dependence are closely related, and loneliness plays a vital role in this relationship, suggesting that mobile phone dependence can be reduced by alleviating university students’ loneliness. These findings enhanced the understanding of the mechanism of mobile phone dependence and provided new perspectives for the prevention and treatment of mobile phone dependence among university students.